Mechanisms and Therapeutic Potential of GPX4 in Pain Modulation - Shiwen Fan; Kaixin Wang; Tianhao Zhang; Daling Deng; Jiwei Shen; Bowen Zhao; Daan Fu; Xiangdong Chen (Pain and Therapy)
Abstract Pain, a complex symptom encompassing both sensory and emotional dimensions, constitutes a significant global public health issue. Oxidative stress is a pivotal factor in the complex pathophysiology of pain, with glutathione peroxidase 4 (GPX4) recognized as a crucial antioxidant enzyme involved in both antioxidant defense mechanisms and ferroptosis pathways. This review systematically explores GPX4’s functions across various pain models, including neuropathic, inflammatory, low back, and cancer-related pain. Specifically, the focus includes GPX4’s physiological roles, antioxidant defense mechanisms, regulation of ferroptosis, involvement in signal transduction pathways, and metabolic regulation. By summarizing current research, we highlight the potential of GPX4-targeted therapies in pain management.